Penerapan model direct instruction untuk meningkatkan kemampuan berpidato peserta didik kelas VI sekolah dasar - Abidah, Aqila Zain; Matsuri, Matsuri (Universitas Sebelas Maret, 2026)
This study aimed to improve the speech-delivery skills of sixth-grade students at SDN 01 Seloromo through the Direct Instruction model. The study was conducted as Classroom Action Research (CAR) over three cycles using the Kemmis and McTaggart model. Each cycle followed five stages: orientation, presentation, structured practice, guided practice, and independent practice. Data were collected through observation, interviews, and performance assessments based on pronunciation, intonation, volume, fluency, and body gestures. Initially, only 33.33% of students met the Minimum Mastery Criteria (KKTP). After implementing the model, student mastery improved to 71.42% in Cycle I, 85.71% in Cycle II, and 90.47% in Cycle III. Teacher activity also increased from 78.33% to 95%, and student engagement rose from 58.33% to 75%. The use of media such as intonation symbols and expression boards helped enhance student performance. The findings suggest that Direct Instruction effectively improves speech skills and can be a useful strategy for teaching public speaking in elementary schools.